Lethal Program of Culture vs the Whole of Presentation. Presentation of Body without Organs - Doda-Wyszyńska,, Agnieszka (Journal of Applied Cultural Studies, 2016)
The culture of signs is a recurrent term in philosophy. It does not allow mindless programs to win. Thanks to it, it is possible to put trust in model, holistic approaches rather than the linguistic determination of meanings. The process of departing from philosophical reflection, which has always been holistic, expressed with the diagram: ideas – notions – definitions, is here reversed. Presentations allow the return to ideas; ideas have more of the imaginary than the symbolic. The concept of the Body without Organs depicts a new form of sensualisation directed not at gaining permanent representations but at the possibilities of switching various functions of experience.